Fabrication and characteristics of oil palm fibre- reinforced polylactic acid composite filled with iron oxide for microwave application - Abdalhadi, Daw Mohammad (2018)
Microwave absorbers generally consist of a filler material inside a polymer matrix. The filler contains one or more elements that do most of the absorbing. Absorbers are used in a wide range of applications to eliminate stray or unwanted radiation that could interfere with a system’s operation. Ferrites is the most common shielding material in the development of absorbing composites. However, ferrites are heavy, corrosive, non-biodegradable and expensive. This project investigates the application of oil palm empty fruit bunch fibres (OPEFB) as an alternative to ferrite fillers for microwave absorbing applications with PLA as the host matrix. OPEFB offer various advantages such as low cost, low density, better thermal, insulating properties and biodegradability. Also PLA has significant advantages including ease of fabrication, zero toxicity, biodegradability, high mechanical strength and thermal plasticity. Different compositions of filler were doped and blended to produce OPEFB-PLA and OPEFB-PLA-Fe2O3 composites via Brabender Plastograph EC blending machine operating at 170°C with rotor speed of 50 rpm for 20 minutes. The total mass of each blended composite was 45g and contained 200 μm size OPEFB fibres. The crystalline structure of the composites was analyzed using X-ray diffraction (XRD) machine. The elemental compositions were examined using Scanning Electron Microscopy (SEM), energy dispersive X-ray analysis (EDX) and Fourier transform infrared (FTIR) techniques. Thermal analyses were carried out using TGA and DTG. The dielectric properties and S-Parameters, were measured using a PNA (N5227) Network Analyzer from 8GHz to 12 GHz for rectangular waveguide and 0.01 GHz to 12 GHz for microstrip at room temperature. The theoretical calculations of the S-Parameters coefficients of the samples were computed using Finite Element Method (FEM) in conjunction with the COMSOL software. The comparison between the measured and calculated scattering parameters was also investigated. The permittivity of the composites was found to be dependent on the mixing ratio between OPEFB, PLA, and Fe2O3. At 10 GHz in the X-band frequencies, the dielectric constants of OPEFB-PLA and OPEFB-PLA-Fe2O3 composites were found to be between 3.04 to 3.36 and 3.14 to 3.7 respectively while the loss factor values were from 0.3 to 0.4 and 0.3 to 0. 346. Both the dielectric constant and loss factor of the OPEFB-PLA OPEFB-PLA-Fe2O3 composites increased with increasing percentages of OPEFB and Fe2O3 fillers. Furthermore, the results obtained from the scattering parameters |S11| and |S21| were used to determine the absorption loss of the different percentages of OPEFB-PLA and OPEFB-PLA-Fe2O3 composites samples, the absorption loss were found at 10 GHz to be from 0.049 to 0.105 and 0.045 to 0.062 respectively. Finally, the effect of the different percentages of OPEFB and Fe2O3 filler on the electric field was investigated by visualizing the electric field distribution pattern of the OPEFB-PLA and OPEFBPLA-Fe2O3 composites samples placed in the rectangular waveguide and placed on the top of microstrip using finite element method.